Method for improving wear resistance through ejector pin hole carburizing and nitriding-laser modification composite strengthening
Through the carburizing and nitriding-laser modified composite strengthening process, the ultra-high hardness gradient field and high residual compressive stress field of the inner surface of the ejection pin hole are constructed, which solves the problem of easy wear of the ejection pin hole in the injection mold, and achieves a significant improvement in wear resistance and an extension of the mold life.
Patent Information
- Application Number
- CN202510204004.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-05-02
AI Technical Summary
The thimble hole of the injection mold is prone to wear during operation, resulting in too large gap between the thimble hole of the mold and the thimble hole, causing flashes and reducing the surface quality of the product.
Carburizing and nitriding-laser modified composite strengthening process is adopted to construct an ultra-high hardness gradient field and high residual compressive stress field on the inner surface of the ejector hole through hot forging, carburizing, nitriding and laser oblique impact to form an effective nanocrystal structure.
It significantly improves the wear resistance of the pin hole, slows down the wear between the hole shafts, extends the service life of the mold, and ensures the surface quality of the injection molded products.
Smart Images

Figure CN119913516A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of material surface treatment, in particular to a method for improving wear resistance through top pinhole carburizing and nitriding-laser modification composite strengthening. Background Art
[0002] Engineering plastics have the advantages of lightweight, good heat and corrosion resistance, and high strength, and can maintain stable performance even in an environment with rapid temperature changes. These characteristics make engineering plastics extremely widely used in the fields of automobiles, medical devices, aerospace, petrochemicals, electrical appliances, and buildings. For example, in the automotive industry, engineering plastics are widely used in steering wheels, instrument covers, and lamp covers. Plastic parts are also widely used in high-tech fields such as aerospace, such as portholes, instrument panels, and other areas. Injection molds can quickly and accurately manufacture plastic parts of various complex shapes. Their processing technology is simple, the molding precision is high, and they can be mass-produced. They are an important part of modern manufacturing. As a key part of the ejection system of the injection mold, the ejector hole of the mold and the ejector are worn during operation due to the relative movement between the ejector hole and the ejector, which makes the gap between the two too large, and it is easy to produce flash, which significantly reduces the surface quality of the product. This study aims to solve the problem of easy wear of the ejector hole of the injection mold, and studies the composite surface modification technology of the ejector hole of the injection mold to improve the wear resistance of the ejector hole, increase the service life of the mold, and ensure the surface quality of the injection molded product, so as to open up new ideas for the development of new technologies for long-life and high-performance manufacturing of injection molds.
[0003] At present, the strengthening processes of small holes mainly include cold extrusion strengthening of slotted bushings, laser shock strengthening, ultrasonic shock strengthening, etc. Patent CN113722825B introduces a design method for an extrusion core rod for hole strengthening. This process determines the maximum fatigue life of the strengthened hole after interference extrusion, and it can be known that the minimum interference extrusion amount under the maximum fatigue life achieves the optimal life improvement. Patent CN102517413 first uses a large spot and high energy laser, and then uses a small spot and low energy laser to impact strengthen the surface of the small hole component to be opened twice, so that the surface to a deeper depth produces better residual compressive stress, and finally punches. Patent CN103014803B introduces a small hole strengthening method combining laser shock and micro-arc oxidation, firstly, the metal sheet is subjected to vertical laser shock, then a hole is opened in the strengthening area, the inner surface of the hole is pretreated and then a ceramic layer is plated. However, these technologies use plastic deformation processes to strengthen the inner wall of the small hole, which has limited effect on the strengthening of the inner wall of the small hole. This patent proposes a carburizing-nitriding-laser oblique impact surface composite modification process to construct an ultra-high hardness gradient field, an ultra-high residual compressive stress field, and effective nanocrystals in the inner surface of the pinhole. Summary of the invention
[0004] The purpose of the present invention is to provide a method for improving the wear resistance of ejector hole by carburizing and nitriding-laser modification composite strengthening, which can improve the surface hardness of the ejector through carburizing and nitriding-ultrasonic impact surface modification process, and introduce high residual compressive stress to slow down the wear between the hole axis. This is because the abrasive particles fall off from the ejector surface and the inner wall of the ejector hole, and the high residual compressive stress can inhibit the formation and expansion of cracks on the sample surface. Under the combined effect of high hardness and high residual compressive stress, the wear between the ejector hole / ejector friction pair is reduced, so that the partial wear depth of the hole mouth is reduced, and finally the purpose of improving the wear resistance of the ejector hole mouth is achieved.
[0005] To achieve the above object, the present invention provides a method for improving wear resistance by carbonitriding and nitriding of ejector pinholes and laser modification composite strengthening, comprising the following steps:
[0006] Step 1: The ejector hole substrate is prepared into a blank by a hot forging process to obtain an ejector hole substrate layer;
[0007] Step 2: Carburizing the ejector pinhole matrix layer prepared in step 1 to obtain a structure with a gradient carbon content, followed by quenching to transform the austenite in the carburized layer into a martensite structure, obtaining a surface structure of a high-carbon martensite structure and a mixed structure of austenite, and finally performing high-temperature tempering, during which the residual austenite and high-carbon martensite are transformed into cryptocrystalline martensite with higher wear resistance, forming a transition layer of cryptocrystalline martensite, and obtaining a carburized ejector pinhole;
[0008] Step 3: subjecting the carburized ejector pinhole obtained in step 2 to ion nitriding treatment to obtain a mixed structure of carbide, nitride and tempered martensite, thereby obtaining a carburized and nitrided ejector pinhole;
[0009] Step 4: The carbonitriding pinhole obtained in step 3 is subjected to surface laser shock modification treatment to obtain a laser modified layer and ultimately a high-energy modified pinhole.
[0010] Preferably, in step S1, the diameter of the ejector hole is 8 mm-15 mm, and the ejector hole is made of H13 steel.
[0011] Preferably, the carburizing gas atmosphere is: C2H2:N2, and the nitriding gas atmosphere is N2:H2=450ml / min:150ml / min.
[0012] Preferably, in step 2, the carburizing working pressure is 680-700 Pa, the carburizing temperature is 925-930° C., and the carburizing time is 5 hours.
[0013] Preferably, in step 3, during the nitriding treatment, the gas pressure is 290Pa-300Pa, the temperature is 470°C-480°C, the nitriding insulation time is 8 hours, and finally the nitriding is cooled with the furnace.
[0014] Preferably, in step 4, the thickness of the nitriding layer in the high-energy modified ejector pinhole is 0-0.1 mm, the thickness of the carburizing layer is 0-1 mm, and the thickness of the laser modified layer is 0-30 μm.
[0015] Preferably, in step 4, the laser power density of the laser shock is in the range of 20.4 to 31.89 GW / cm 2 , the laser energy is 8J, the spot diameter is 3mm, the pulse width is 20ns, the pulse frequency is 5Hz, and the peak pressure of the laser shock wave is 6.8~7.3GPa.
[0016] A pinhole is prepared by a method for improving wear resistance through carburizing and nitriding of a pinhole and laser modification composite strengthening.
[0017] Therefore, the present invention adopts the above-mentioned method of improving the wear resistance of the ejector hole by carburizing and nitriding-laser modification composite strengthening, and improves the surface hardness of the ejector through the carburizing and nitriding-ultrasonic impact surface modification process, and introduces high residual compressive stress to slow down the wear between the hole axis. This is because the abrasive particles fall off from the ejector surface and the inner wall of the ejector hole, and the high residual compressive stress can inhibit the formation and expansion of cracks on the surface of the sample. Under the combined action of high hardness and high residual compressive stress, the wear between the ejector hole / ejector friction pair is reduced, so that the partial wear depth of the hole mouth is reduced, and finally the purpose of improving the wear resistance of the ejector hole hole mouth is achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a vacuum carburizing process;
[0019] Figure 2 It is an ion nitriding process;
[0020] Figure 3 This is a schematic diagram of laser oblique impact pinhole;
[0021] Figure 4 Schematic diagram of the surface structure of the ejector pinholes after carburizing-nitriding-laser oblique impact composite modification;
[0022] Figure 5 Wear depth of ejector hole: Figure 5 (a) Untreated sample; Figure 5 (b) Nitriding-laser specimen. DETAILED DESCRIPTION
[0023] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0024] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0025] Since the laser beam is irradiated to the target surface at a certain angle during the laser oblique impact process, the shape of the light spot projected onto the target surface changes from a circle to an ellipse. When the laser spot is a circle, let r be the radius of the laser spot when it is a circle. When the laser beam is incident obliquely, the circular laser spot becomes an elliptical spot. At this time, the incident angle is set to θ, and the minor axis radius of the ellipse is set to b, then b = r, and the major axis radius of the ellipse a = b / cosθ. Since the projection area has changed and the law of conservation of laser energy is observed, the energy density of the laser will change. This law is obtained according to the change formula of the Bouguer-Lambert law:
[0026]
[0027] Where: I1 is the laser energy density (J / m 2 ), where I1 = I2r 2 / ab, I2 is the laser energy density vertically incident on the material surface, a and b are the major and minor axes of the elliptical spot when the laser spot is projected onto the impact surface (mm); A is the absorption capacity of the material, A=IR (R is the reflectivity); β(x) is the absorption coefficient of the laser in the medium (x: positive from the material surface to the inside).
[0028] When the laser-induced plasma shock wave is greater than the elastic limit of the target material, plastic deformation occurs on the surface of the material. According to the elastic limit calculation formula given by Johnson:
[0029]
[0030] Where: HEL elastic limit (GPa); material Poisson's ratio υ is 0.3; is the dynamic compressive yield strength of the material at high strain rate (MPa). The dynamic yield strength of steel can be obtained by the formula:
[0031]
[0032] in, Represents the dynamic yield strength.
[0033] The dynamic yield strength of H13 steel calculated by the above formula is 1695MPa, and the calculation formula of elastic limit (HEL) is About 2.96 GPa. Since the peak pressure of laser-induced shock is best at 2HEL to 2.5HEL, the peak pressure of the material shock wave is calculated to be 5.92 GPa to 7.4 GPa.
[0034] The relationship between laser power density and plasma shock wave pressure peak proposed by Fabbro et al. is:
[0035]
[0036] Where P(t) is the peak pressure of the shock wave (GPa); α is the internal energy conversion coefficient, which is α=0.2; Z is the acoustic impedance (cm 2 ·s); I0 is the laser power density.
[0037] The laser power density of the material in formula (1-4) satisfies the following relationship:
[0038]
[0039] Where E is the laser energy (J); r is the spot radius (mm); τ is the laser pulse width (ns). The laser power density range is determined to be 20.4 to 31.89 GW / cm 2 , the laser energy is selected to be 8J, the spot diameter is 3mm, the pulse width is 20ns, the pulse frequency is set to 5Hz, and the peak pressure of the laser shock wave is selected to be 7GPa.
[0040] When the laser spot diameter is 3 mm, the short axis radius is set to b, and the long axis radius a=b / cosθ. It is found that when the angle between the laser beam and the normal is 15°, 30°, and 45°, the spot diameters are 3.12 mm, 3.46 mm, and 4.24 mm, respectively.
[0041] In summary, during the laser oblique impact process of the ejector hole, the edge of the ejector hole is firstly impacted at multiple points in a circular path using a laser incident angle of 15°, with an overlap rate of 50%; secondly, a laser incident angle of 30° is used to perform an annular impact on the ejector hole, with an overlap rate of 50%; finally, a laser incident angle of 45° is used to perform an annular impact on the ejector hole, with an overlap rate of 50%; the center spacing between different annular impact areas is 1.5 mm.
[0042] Example 1
[0043] A method for improving wear resistance by carbonitriding and nitriding of ejector pinholes and laser modification composite strengthening, comprising the following steps:
[0044] (1) Nitriding: The nitriding gas atmosphere is N2:H2=450ml / min:150ml / min, the gas pressure is 290Pa, the temperature is 480℃, the insulation time is 8 hours, and finally the furnace is cooled.
[0045] (2) Laser oblique impact: The laser spot diameter is 3 mm, the overlap rate is 50%, the pulse energy is set to 8 J, the laser incident angle is 15°, the laser pulse duration is 20 ns, the wavelength is 1064 nm, black glue is used as the absorption layer, and 2 mm thick flowing water is used as the constraint layer.
[0046] Example 2
[0047] A method for improving wear resistance by carbonitriding and nitriding of ejector pinholes and laser modification composite strengthening, comprising the following steps:
[0048] (1) Nitriding: The nitriding gas atmosphere is N2:H2=450ml / min:150ml / min, the gas pressure is 290Pa, the temperature is 480℃, the insulation time is 8 hours, and finally the furnace is cooled.
[0049] (2) Laser oblique impact: The laser spot diameter is 3 mm, the overlap rate is 50%, the pulse energy is set to 8 J, the laser incident angle is 30°, the laser pulse duration is 20 ns, the wavelength is 1064 nm, black glue is used as the absorption layer, and 2 mm thick flowing water is used as the constraint layer.
[0050] Example 3
[0051] A method for improving wear resistance by carbonitriding and nitriding of ejector pinholes and laser modification composite strengthening, comprising the following steps:
[0052] (1) Nitriding: The nitriding gas atmosphere is N2:H2=450ml / min:150ml / min, the gas pressure is 290Pa, the temperature is 480℃, the insulation time is 8 hours, and finally the furnace is cooled.
[0053] (2) Laser oblique impact: The laser spot diameter is 3 mm, the overlap rate is 50%, the pulse energy is set to 8 J, the laser incident angle is 45°, the laser pulse duration is 20 ns, the wavelength is 1064 nm, black glue is used as the absorption layer, and 2 mm thick flowing water is used as the constraint layer.
[0054] Comparative Example 1
[0055] A method for improving wear resistance by carbonitriding and nitriding of ejector pinholes and laser modification composite strengthening, comprising the following steps:
[0056] (1) Nitriding: The nitriding gas atmosphere is N2:H2=450ml / min:150ml / min, the gas pressure is 290Pa, the temperature is 480℃, the insulation time is 8 hours, and finally the furnace is cooled.
[0057] (2) Laser oblique impact: The laser spot diameter is 3 mm, the overlap rate is 50%, the pulse energy is set to 8 J, the laser incident angle is 0°, the laser pulse duration is 20 ns, the wavelength is 1064 nm, black glue is used as the absorption layer, and flowing water with a thickness of 2 mm is used as the constraint layer.
[0058] Comparative Example 2
[0059] A method for improving wear resistance by carbonitriding and nitriding of ejector pinholes and laser modification composite strengthening, comprising the following steps:
[0060] (1) Laser oblique impact: The laser spot diameter is 3 mm, the overlap rate is 50%, the pulse energy is set to 8 J, the laser incident angles are 15°, 30°, and 45°, the laser pulse duration is 20 ns, the wavelength is 1064 nm, black glue is used as the absorption layer, and 2 mm thick flowing water is used as the constraint layer.
[0061] (2) Nitriding: The nitriding gas atmosphere is N2:H2=450ml / min:150ml / min, the gas pressure is 290Pa, the temperature is 480℃, the insulation time is 8 hours, and finally the furnace is cooled.
[0062] The hardness and residual stress of five groups of samples treated with different processes were tested, and the results are shown in Table 1:
[0063] Table 1 Surface hardness and residual stress of plane specimens
[0064] performance Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Surface hardness (HV) 1334 1294 1278 1348 1024 Surface residual stress (MPa) -1033 -898 -884 -1067 -681
[0065] Finally, the inner wall of the ejector hole can have high hardness and high residual compressive stress. Its wear resistance can be verified by the hole-shaft accelerated friction and wear test. This experiment sets the ejector / ejector hole to serve 1 million times. According to the relevant parameters of the hole-shaft accelerated wear and wear tester, it can be calculated that the wear test time is about 70 hours (about 1,008,000 times). During the experiment, a pressure plate weighing about 8kg is installed on the upper end of the ejector, so that each ejector is loaded with a demolding force of about 20N. Finally, the wear depth of the hole mouth is observed by laser confocal. The results are as follows: Figure 5 As shown, the wear resistance of the ejector pin hole can be effectively improved.
[0066] Therefore, the present invention adopts the above-mentioned method of carbonitriding and nitriding-laser modification composite strengthening of ejector pinholes to effectively improve the wear resistance of ejector pinholes.
[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for improving wear resistance by carbonitriding and nitriding of ejector pinholes and laser modification composite strengthening, characterized in that: The following steps are involved: Step 1: The ejector hole substrate is prepared into a blank by a hot forging process to obtain an ejector hole substrate layer; Step 2: Carburizing the ejector pinhole matrix layer prepared in step 1 to obtain a structure with a gradient carbon content, followed by quenching to transform the austenite in the carburized layer into a martensite structure, obtaining a surface structure of a high-carbon martensite structure and a mixed structure of austenite, and finally performing high-temperature tempering, during which the residual austenite and high-carbon martensite are transformed into cryptocrystalline martensite with higher wear resistance, forming a transition layer of cryptocrystalline martensite, and obtaining a carburized ejector pinhole; Step 3: subjecting the carburized ejector pinhole obtained in step 2 to ion nitriding treatment to obtain a mixed structure of carbide, nitride and tempered martensite, thereby obtaining a carburized and nitrided ejector pinhole; Step 4: The carbonitriding pinhole obtained in step 3 is subjected to surface laser shock modification treatment to obtain a laser modified layer and ultimately a high-energy modified pinhole.
2. The method for improving wear resistance by carbonitriding and nitriding of ejector pinholes-laser modification composite strengthening according to claim 1, characterized in that: In step S1, the diameter of the ejector hole is 8mm-15mm, and the material of the ejector hole is H13 steel.
3. The method for improving wear resistance by carbonitriding and nitriding of ejector pinholes-laser modification composite strengthening according to claim 1, characterized in that: The carburizing gas atmosphere is: C2H2:N2, and the nitriding gas atmosphere is N2:H2=450ml / min:150ml / min.
4. The method for improving wear resistance by carbonitriding and nitriding of ejector pinholes-laser modification composite strengthening according to claim 1, characterized in that: In step 2, the carburizing working pressure is 680-700 Pa, the carburizing temperature is 925-930° C., and the carburizing time is 5 hours.
5. The method for improving wear resistance by carbonitriding and nitriding of ejector pinholes-laser modification composite strengthening according to claim 1, characterized in that: In step 3, during the nitriding treatment, the gas pressure is 290Pa-300Pa, the temperature is 470℃~480℃, the nitriding insulation time is 8 hours, and finally the furnace is cooled.
6. The method for improving wear resistance by carbonitriding and nitriding of ejector pinholes-laser modification composite strengthening according to claim 1, characterized in that: In step 4, the thickness of the nitriding layer in the high-energy modified ejector pinhole is 0-0.1 mm, the thickness of the carburizing layer is 0-1 mm, and the thickness of the laser modified layer is 0-30 μm.
7. The method for improving wear resistance by carbonitriding and nitriding of ejector pinholes-laser modification composite strengthening according to claim 1, characterized in that: In step 4, the laser power density of the laser shock ranges from 20.4 to 31.89 GW / cm 2 , the laser energy is 8J, the spot diameter is 3mm, the pulse width is 20ns, the pulse frequency is 5Hz, and the peak pressure of the laser shock wave is 6.8~7.3GPa.
8. The ejector pinhole prepared by the method for improving wear resistance by carbonitriding and nitriding of ejector pinholes-laser modification composite strengthening according to any one of claims 1 to 7.
Citation Information
Patent Citations
A Small Pore Strengthening Method Combining Laser Shock and Micro-arc Oxidation
CN103014803B
Extrusion mandrel for hole strengthening and design method thereof, hole strengthening system
CN113722825B
Cited By
Thimble anti-fatigue strengthening method based on multi-section variable temperature treatment
CN121496150A